Evaluation of soybean selection and sowing date in a continuous cover relay-cropping system with pennycress - Gesch, Russ W.; Mohammed, Yesuf Assen; Matthees, Heather L. (Frontiers in Sustainable Food Systems, 2023)
Pennycress (Thlaspi arvense L.) is a new winter annual oilseed crop that can be integrated as a “cash cover crop” in Midwestern USA cropping systems. Relay-cropping pennycress with soybean [Glycine max (L.) Merr.] has been shown as an effective way to produce three crops over 2 years while providing living cover on the agricultural landscape nearly year-round. However, management improvements are needed to optimize pennycress and soybean production in this new system. A 2-year field study was conducted to evaluate three soybean interseeding dates (based on pennycress growth stage) and three soybean cultivars (varied in maturity date) on the overall productivity of this relay system. Interseeding dates were SD1 (rosette stage), SD2 (bolting stage), and SD3 (initial flowering), and soybean cultivars were MG0.2 (early), MG1.1 (standard), and MG1.7 (late). In the second season, relaying soybean reduced pennycress seed yield compared with its monocrop counterpart, but the reduction was lowest (23%) at SD2. Cultivar maturity group impacted soybean seed yields in the relay system, which for MG0.2, MG1.1, and MG1.7 averaged 2,589, 3,196, and 3,445 kg ha−1, respectively. Although there was soybean yield drag associated with relay cropping, the seed yield of the MG1.7 cultivar relay interseeded at SD2 was not significantly different from a monocropped MG1.1 soybean using conventional practice (CP; winter fallow, no pennycress). The results indicate that relay interseeding of longer maturity (MG1.7) soybean for the region at the bolting stage (SD2) of pennycress optimized overall system productivity while keeping the continuous living cover on the agricultural landscape. More research will likely be needed to improve soybean selection and management regionally for this unique relay system.